Primary Care Severe Asthma Registry and Education Project (PCSAR-EDU): Phase 1 – an e-Delphi for registry definitions and indices of clinician behaviour - Michelle Greiver; Babak Aliarzadeh; Rahim Moineddin; Teresa To; Braden O'Neill; Kenneth R Chapman; Katrina A D'Urzo; Itamar E Tamari; M Reza Maleki-Yazdi; Ross EG Upshur; Lana Biro; Kulamakan Kulasegaram; et al. (BMJ Open)
Introduction Although most asthma is mild to moderate, severe asthma accounts for disproportionate personal and societal costs. Poor co-ordination of care between primary care and specialist settings is recognised as a barrier to achieving optimal outcomes. The Primary Care Severe Asthma Registry and Education (PCSAR-EDU) project aims to address these gaps through the interdisciplinary development and evaluation of both a ‘real-world’ severe asthma registry and an educational programme for primary care providers. This manuscript describes phase 1 of PCSAR-EDU which involves establishing interdisciplinary consensus on criteria for the: (1) definition of severe asthma; (2) generation of a severe asthma registry and (3) definition of an electronic-medical record data-based Clinician Behaviour Index (CBI).Methods and analysis In phase 1, a modified e-Delphi activity will be conducted. Delphi panellists (n≥13) will be invited to complete a 30 min online survey on three separate occasions (i.e., three separate e-Delphi ‘rounds’) over a 3-month period. Expert opinion will be collected via an open-ended survey (‘Open’ round 1) and 5-point Likert scale and ranking surveys (‘Closed’ round 2 and 3). A fourth and final Delphi round will occur via synchronous meeting, whereby panellists approve a finalised ideal ‘core criteria list’, CBI and corresponding item weighting.Ethics and dissemination Ethical approval has been obtained for the activities involved in phase 1 from the University of Toronto’s Human Research Ethics Programme (approval number 39695). Future ethics approvals will depend on information gathered in the proceeding phase; thus, ethical approval for phase 2 and 3 of this study will be sought sequentially. Findings will be disseminated through conference presentations, peer-reviewed publications and knowledge translation tools.